Psychometric properties and domains of postural control tests for individuals with knee osteoarthritis: a systematic review. Issue 2 (June 2020) - French, Helen P.; Hager, Charlotte K.; Venience, Anne; Fagan, Ryan; Meldrum, Dara
Abstract : Individuals with knee osteoarthritis (OA) commonly demonstrate impaired postural control. We aimed to systematically review psychometric properties of tests that assess postural control in people with knee OA and secondly, to determine domains of postural control measured by these tests. PubMed, CINAHL, Embase and Web of Science databases were searched to January 2019. Two independent review authors screened references according to eligibility criteria. The Consensus-based Standards for the selection of health Measurement Instruments were used to evaluate study methodological quality. Postural control tests identified from included studies were assessed to determine postural control constructs using the Systems Framework for Postural Control identifying nine domains. Following the screening of 2643 references, five cross-sectional studies and one longitudinal study (n = 408) were included. Four studies evaluated reliability, validity or responsiveness of three clinical measures: Community Balance and Mobility Scale, Star Excursion Balance Test and Tinetti Performance Oriented Mobility Assessment. Two assessed reliability or validity of a force platform. Results showed that evidence for reliability, validity and responsiveness of all these postural measures is limited. The most common domain of postural control assessed was 'static stability'. No study used measures that evaluated all nine postural control domains. Our results highlight limited investigation of psychometric properties specific to postural control in knee OA. The few existing ones have limitations regarding psychometric robustness and completeness regarding different domains of postural control. Future research should focus on verifying the quality of existing tools to evaluate postural control in knee OA for research and clinical purposes.